A prospective, multi-centre US clinical trial to determine accuracy of FebriDx point-of-care testing for acute upper respiratory infections with and without a confirmed fever. (4th July 2018) - Shapiro, Nathan I.; Self, Wesley H.; Rosen, Jeffrey; Sharp, Stephan C.; Filbin, Michael R.; Hou, Peter C.; Parekh, Amisha D.; Kurz, Michael C.; Sambursky, Robert
Abstract: Background: FebriDx is a 10-minute disposable point-of-care test designed to identify clinically significant systemic host immune responses and aid in the differentiation of bacterial and viral respiratory infection by simultaneously detecting C-reactive protein (CRP) and myxovirus resistance protein A (MxA) from a fingerstick blood sample. FebriDx diagnostic accuracy was evaluated in the emergency room and urgent care setting. Methods: A prospective, multicentre, observational cohort study of acute upper respiratory tract infections (URIs), with and without a confirmed fever at the time of enrolment, was performed to evaluate the diagnostic accuracy of FebriDx to identify clinically significant bacterial infection with host response and acute pathogenic viral infection. The reference method consisted of an algorithm with physician override that included bacterial cell culture, respiratory PCR panels for viral and atypical pathogens, procalcitonin, and white blood cell count. Results: Among 220 patients enrolled, 100% reported fever 100.5°F within the last 72 hours while 55% had a measured hyperthermia (T > 100.4) at the time of enrolment. FebriDx demonstrated a sensitivity of 95% (95% CI: 77–100%), specificity of 94% (88–98%), PPV of 76% (59–87%), and a NPV of 99% (93–100%). Conclusion: FebriDx may identify clinically significant bacterial URI's and supports outpatient antibiotic decisions. Key messages: FebriDx is an outpatient POC test designed to identify a clinically significant systemic host immune response and aid in the differentiation of viral and bacterial infection through rapid measurement of MxA and CRP from a fingerstick blood sample. FebriDx test was determined to be an accurate test, with a 85% sensitivity, 93% specificity and 97% NPV to rule out bacterial infection for any patient presenting with symptoms and reported fever within the prior 3 days, and when confirming fever (hyperthermia) at the time of testing, the test was even more sensitive (95%) and specific (94%) with a 99% NPV. FebriDx may support antibiotic stewardship by rapidly identifying clinically significant bacterial URIs.